Trends in Neisseria meningitidis serogroups amongst patients with suspected cerebrospinal meningitis in the meningitis belt of Ghana: a 5-year retrospective study - Stebleson Azure; Abass Abdul-Karim; Braimah Baba Abubakari; John B. Eleeza; Daron Davies A. Agboyie; Enoch Weikem Weyori; Jun Yong Choi (BMC Infectious Diseases, 2023)
Abstract Background Serogroup A Neisseria meningitidis was the major cause of meningococcal meningitis epidemics in the African meningitis belt before 2010 when the monovalent meningococcal A conjugate vaccine (MenAfriVac) was introduced in the region. Therefore, this study aimed to establish the trends in N. meningitidis serogroups from 2016 to 2020 in Ghana’s meningitis belt. Methods Polymerase chain reaction (PCR) confirmed laboratory results of suspected cases of cerebrospinal meningitis from January, 2016 to March, 2020 were obtained from the Tamale Public Health Laboratory. The data were subjected to trend analysis using Statistical Package for the Social Sciences version 25. Differences between discrete variables were analyzed using the Cochran–Armitage trend test. Results Of the 2,426 suspected cases, 395 (16.3%) were confirmed positive for N. meningitidis using PCR. Serogroup X showed a significant upward trend (P < 0.01), and serogroup W showed a downward trend (P < 0.01). However, no significant trend was observed for any other serogroup. Conclusion This study showed the emergence of serogroup X, a non-vaccine type, as the predominant N. meningitidis serogroup in the wake of a declining serogroup W in Ghana’s meningitis belt.